Substrate temperature effect on the photophysical and microstructural properties of fluorine-doped tin oxide nanoparticles. (July 2017) - Abideen, Ibiyemi; Gbadebo, Yusuf; Abass, Faremi
Abstract: Transparent conducting oxide of fluorine-doped tin oxide (FTO) thin films was deposited from chemical solutions of tin chloride and ammonium fluoride using streaming process for electroless and electrochemical deposition (SPEED) at substrate temperature 450, 500, and 530 °C respectively. The effect of substrate temperatures on the microstructural properties such as crystallite size, dislocation density, micro strain, volume of the unit cell, volume of the nanoparticles, number of the unit cell, bond length and the lattice constants were examined using XRD technique. Only reflections from (110) and (200) planes of tetragonal SnO2 crystal structure were obvious. The peaks are relatively weak indicating that the deposited materials constitute grains in the nano dimension. Hall measurements, which were done using van der Pauw technique, showed that the FTO films are n-type semiconductors. The most favorable electrical values were achieved for the film grown at 530 °C with low resistivity of 7.64 × 10 −4 Ω·cm and Hall mobility of –9.92 cm 2 /(V·s).